Building boundary-crossers in clinical-translational research: An exploratory study of a novel communication intervention - Carrie Cameron; Irene Rull-Garcia; Laura G. Meyer; Jose-Armando Fernandez-Guerrero; Erin K. Dahlstrom; Christine Bell; Christine Pribbenow (Journal of Clinical and Translational Science)
Abstract